The Web sites of New Zealand non-governmental development organisations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, School of People, Environment and Planning, College of Humanities and Social Sciences - Webster, John (Massey University, 2002)
New Zealand Non-Governmental Development Organisations (NGOs) are facing challenges in areas of accountability, effectiveness, efficiency, and communication and sharing of information, both internally and externally. The technology of the World Wide Web has the ability to assist organisations in facing these challenges. This study examines the Web sites of NZ NGOs and evaluates them against accepted best practice criteria to see whether the sites are effective in meeting the challenges and enhancing the activities of the organisations. Looking at how NZ NGOs are currently using the Web and comparing their efforts with current 'best practice' will help organisations understand how establishing and maintaining a Web presence can best address the challenges.
Keywords: New Zealand; World Wide Web; Web sites -- Design -- Evaluation; Non-governmental organizations